PERAN BUDAYA PENDIDIKAN DALAM MENUMBUHKAN NILAI-NILAI MORAL - Arif Ma’mun Rifa’i (Institut Agama Islam Ngawi, 2022)
Abstract Culture in education is a culture that is built on institutions that have certain characteristics used by education providers with the values ​​adopted by teachers and employees in these educational institutions. In educational systems, culture is important to consider matching to the aim of education with contain character values. Thus institutions can graduate generations who are aware that the social values are so important in their live. Thus, with the creation of this awareness, generations of humans are awakened to uphold moral values ​​in the social order of society. Moral values are so important and inevitably internalized in each individual in order to be actualized in the practice of life. Therefore, developing the future or young generation that has good characters is our responsibility. Education is an effort to maintain the noble moral values ​​of a nation. Education aims to produce intellectual achievement by growing and maintaining personality. This article discusses how educational culture can play a role in influencing and contributing to growing moral values. Keywords: Culture, Education, Moral Values